Geometry Study of an Isotropic 3D Silicon Hall Sensor. (2015) - Sander, C.; Leube, C.; Aftab, T.; Ruther, P.; Paul, O.
Abstract: This paper reports a geometry study to evaluate the influence of design parameters on the performance of a novel three-dimensional (3D) Hall sensor. The focus is in particular on the isotropy of the sensitivities for the three spatial components of the magnetic field and the inherent offset voltage. The silicon Hall device has the shape of a hexagonal prism with symmetric sets of three contacts located on its top and bottom surfaces. By sending currents obliquely across the sensitive volume one is able to operate the device as three identical and mutually orthogonal Hall sensors. We demonstrate a design with isotropic sensitivities of about 34.3 mV/VT and an inherent offset of 2 mV which can be further reduced by an appropriate sensor redesign.